Essentials of PEM Fellowship Part 2: The Profession in Entrustable Professional Activities. Issue 6 (June 2016) - Hsu, Deborah; Nypaver, Michele; Fein, Daniel M.; McAneney, Constance; Santen, Sally; Nagler, Joshua; Zuckerbraun, Noel; Roskind, Cindy Ganis; Reynolds, Stacy; Zaveri, Pavan; Stankovic, Curt; House, Joseph B.; et al.
Abstract : Abstract: This article is the second in a 7-part series that aims to comprehensively describe the current state and future directions of pediatric emergency medicine (PEM) fellowship training from the essential requirements to considerations for successfully administering and managing a program to the careers that may be anticipated upon program completion. This article describes the development of PEM entrustable professional activities (EPAs) and the relationship of these EPAs with existing taxonomies of assessment and learning within PEM fellowship. It summarizes the field in concepts that can be taught and assessed, packaging the PEM subspecialty into EPAs.